2015
DOI: 10.3390/polym7081389
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of High Performance Cyclic Olefin Polymers (COPs) with Ester Group via Ring-Opening Metathesis Polymerization

Abstract: Novel ester group functionalized cyclic olefin polymers (COPs) with high glass transition temperature, high transparency, good mechanical performance and excellent film forming ability have been achieved in this work via efficient ring-opening metathesis copolymerization of exo 4,4a,9,9a,10(1′, and comonomers (5-norbornene-2-yl methylacetate (NMA), 5-norbornene-2-yl methyl 2-ethylhexanoate (NME) or 5-norbornene-2-yl methyldodecanoate (NMD)) utilizing the Grubbs first generation catalyst, Ru(CHPh)(Cl)2(PCy3)2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…M2 has been verified to be very effective in improving the T g of COP and its synthesis and structural analysis has been described in detail according to our previous reports (Scheme b) . Based on this, it was desirable to synthesize a novel monomer to further increase its steric hindrance for achieving higher T g of COP.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…M2 has been verified to be very effective in improving the T g of COP and its synthesis and structural analysis has been described in detail according to our previous reports (Scheme b) . Based on this, it was desirable to synthesize a novel monomer to further increase its steric hindrance for achieving higher T g of COP.…”
Section: Resultsmentioning
confidence: 93%
“…For instance, when 1,4,5,8‐dimethano‐1,2,3,4,4a,5,8,8a‐octahydronaphtalene (DMON) is used as a monomer, the T g of hydrogenated DMON polymer (Scheme ) is as high as 174 °C, while the T g can reach up to 188 °C of a hydrogenated tricyclopentadiene polymer (Scheme ) . Very recently, we have obtained a novel COP by ROMP of exo ‐1,4,4a,9,9a,10‐hexahydro‐9,10(1′,2′)‐benzeno‐l,4‐methano‐anthracene ( M2 in Scheme ) and subsequent hydrogenation with very high T g value of about 220 °C . To the best of our knowledge, this value is the highest T g reported for COP prepared via ROMP approach.…”
Section: Introductionmentioning
confidence: 99%
“…The second pathway deals with the ring-opening metathesis polymerization (ROMP) of various cyclic monomers, followed by hydrogenation, and gives rise to COP [63][64][65]. Those copolymers are unsaturated and generally exhibit good solubility in various solvents.…”
Section: Cyclic Olefin Copolymers (Coc) Development Of Cyclic Olefin mentioning
confidence: 99%
“…The author reported that the dispersion of the PCL phase in the EP matrix depended on the EP type, and the study revealed a healing efficiency of up to 80%, with a healing temperature of 80 • C. In 2009, Luo et al [23] studied similar EP/PCL blends and were able to reach a healing efficiency above 100%, with a healing temperature of 190 • C. Inspired by this works, our group in 2020 for the first time investigated the thermal mending potential of a cyclic olefin copolymer (COC) in an EP matrix [21]. COC is an attractive class of amorphous thermoplastic polymers, thanks to their high transparency, good heat resistance, low moisture absorption, good chemical resistance, low density, and elevated stiffness [12,[24][25][26][27][28]. Several EP/COC blends were prepared by mechanically mixing the COC powder and EP resin in the uncured state.…”
Section: Introductionmentioning
confidence: 99%